ISOLASI DAN IDENTIFIKASI BAKTERI ASAM LAKTAT PADA CAECUM AYAM DAGING (Isolation and ldentitication of Lactic Acid Bacteria in the Broiler's Caecum) - Sri Sumarsih; T. Yudiarti; C.S. Utama; E. S. Rahayu; E. Harmayani (JURNAL KESEHATAN, 2009)
Abstract Lactic acid bacteria is one of natural microbe which is often used as fermentation agent. The Purpose of this researchwas isolated and identified lactic acid bacteria in broiler's caecum. Exploration experimental method by 6 repetition with 2 sub research was used. The ldentification of Lactic acid bacteria was based on morphological, biochemical and physiological of the character. The morphological characteristic were shape cell and gram test. The biochemical characteristic was catalase test. The physiological characteristic was clear zone test. The result obtained l2 isolates of Lactic acid bacteria, rod and coccus , gam positive, catalase negative and showed clear zone colony at lok CaCOt in MRS. That were early characteristic of lactic acid bacteria which were apparenly as genus of Lactobacillus and Leuconostoc. Keywords : caecum, Lactic acid bacteria